Language : the Linguistic Essays of William Diver. - Huffman, Alan (BRILL, 2011)
In these newly edited, annotated, and contextualized foundational linguistic works, many previously unpublished, the late William Diver of Columbia University radically analyzes language as a structure shaped by communicative function and by characteristics of its human users.